Feasibility and safety of transesophageal endoscopic resection for benign mediastinal tumors - Jia YU; Liyun MA; Wei SU; Shengli LIN; Quanlin LI; Pinghong ZHOU; Pingting GAO (Zhongguo Linchuang Yixue, 2025)
Objective To explore the feasibility, safety, and efficacy of transesophageal endoscopic surgery for mediastinal tumors. Methods A retrospective analysis was conducted on the clinical data of 17 patients who underwent transesophageal endoscopic resection for benign mediastinal tumors at the Endoscopy Center of Zhongshan Hospital, Fudan University, between January 1, 2016 and December 31, 2024. Epidemiological characteristics, surgical parameters, adverse events, and follow-up outcomes were analyzed. Results Among the 17 patients, there were 9 males and 8 females, with an average age of (42.4±14.5) years and an average tumor size of (2.6±1.6) cm. Pathological types included esophageal duplication cysts (6 cases, 35.3%), bronchogenic cysts (5 cases, 29.4%), gastroenteric cysts (3 cases, 17.6%), schwannomas (2 cases, 11.8%), and lymphangioma (1 case, 5.9%). Fourteen patients (82.4%) underwent submucosal tunneling endoscopic resection (STER), 3 patients (17.6%) underwent natural orifice transluminal endoscopic mediastinal surgery. All surgeries were successfully completed without conversion to open surgery. En bloc resection was achieved in 11 patients (64.7%), with an average operative time of (60.9±32.6) min. No intraoperative bleeding or mucosal injury occurred, and 4 patients (23.5%) experienced minor complications (pneumothorax, fever, recurrent laryngeal nerve injury), all of which resolved with conservative treatment. The average postoperative hospital stay was (3.2±1.5) days, and no recurrence was observed during the follow-up period. ConclusionsTransesophageal endoscopic resection of benign mediastinal tumors is a safe, effective, and minimally invasive treatment method. Further validation of its efficacy and safety through large-scale prospective studies is warranted.